2021
DOI: 10.3390/ma14092093
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Er:YAG Laser on a Shear Bond Strength Value of Orthodontic Brackets to Enamel—A Preliminary Study

Abstract: We sought to evaluate the effects of Er:YAG laser (LightTouch, LightInstruments, Israel) conditioning on enamel roughness and shear bond strength of orthodontic brackets on enamel. Eighteen human molars (n = 9) and premolars (n = 9), were divided into 3 groups depending on the enamel conditioning method; Er:YAG laser (G1, n = 6), conventional etching with 37% orthophosphoric acid (G2, n = 6), Er:YAG laser combined with conventional etching (G3, n = 6). Er:YAG laser parameters were as follows: energy: 100 mJ, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…9,10 The use of erbium lasers has been explored as an alternative method for debonding of ceramic appliances from natural teeth and implants, 2,[11][12][13] including removal of translucent restorative materials such as composite restorations, 14,15 fiber reinforced composite posts, 16 veneers, [11][12][13] and orthodontic brackets. 10,[17][18][19] The light emitted by erbium lasers, such as Erbium, Chromium-doped Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) and Erbium-doped Yttrium Aluminum Garnet (Er:YAG) lasers carrying wavelengths of 2780 nm and 2940 nm, respectively, can be transmitted through the translucent ceramic materials and selectively absorbed by water molecules and residual monomers in luting cements, thus resulting in the vaporization of these molecules and debonding of the cement. 5,16,20 This method offers many advantages, however its efficiency can be affected by several clinical operating factors including chemical composition, shade and thickness of the cement, type, shade, opacity, and thickness of the ceramic restoration, and laser parameters such as power, pulse duration, and frequency.…”
mentioning
confidence: 99%
“…9,10 The use of erbium lasers has been explored as an alternative method for debonding of ceramic appliances from natural teeth and implants, 2,[11][12][13] including removal of translucent restorative materials such as composite restorations, 14,15 fiber reinforced composite posts, 16 veneers, [11][12][13] and orthodontic brackets. 10,[17][18][19] The light emitted by erbium lasers, such as Erbium, Chromium-doped Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) and Erbium-doped Yttrium Aluminum Garnet (Er:YAG) lasers carrying wavelengths of 2780 nm and 2940 nm, respectively, can be transmitted through the translucent ceramic materials and selectively absorbed by water molecules and residual monomers in luting cements, thus resulting in the vaporization of these molecules and debonding of the cement. 5,16,20 This method offers many advantages, however its efficiency can be affected by several clinical operating factors including chemical composition, shade and thickness of the cement, type, shade, opacity, and thickness of the ceramic restoration, and laser parameters such as power, pulse duration, and frequency.…”
mentioning
confidence: 99%
“…According to Reynold et al, 6 to 8 MPa is the range for appropriate bond forces in orthodontics [ 13 , 14 ]. According to Kiryk et al, using the Erbium YAG laser in addition to traditional etching increases the bonding of various composites to tooth structures [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it seems to be of advantage when laser-cut tooth surfaces are additionally conditioned with phosphoric acid [ 32 ]. In this regard, Kiryk et al clearly showed that Er:YAG laser-based preparation in combination with conventional acid conditioning results in improved adhesion properties [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the classification of Silverstone, type I etching pattern are afflicted with the most superior adhesive properties [ 49 , 50 ]. As a result of Er:YAG laser conditioning, similar structures compared to Silverstone’s type III patterns are received which are characterized by enamel prisms with damaged peripheral and central regions [ 27 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%